A low-temperature denitration catalyst and preparation method thereof

By using catalysts with components such as iridium oxide under low temperature conditions, combined with modified graphene and zirconium oxide, the problems of low-temperature flue gas denitrogenation efficiency and easy wear of the catalyst are solved, and high-efficiency and low-energy consumption NOx detachment is achieved In addition, it is suitable for the steel and cement industries.

CN117019144BActive Publication Date: 2025-01-14SHANGHAI HANYU ENVIRONMENTAL PROTECTION MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310998216.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-01-14
Estimated Expiration
2043-08-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove NOx from flue gas under low temperature conditions, and traditional medium and high temperature catalysts consume a lot of energy and generate high carbon emissions. The catalysts are prone to blockage and wear, and have a short service life, especially in the steel and cement industries. The problem of denitrification.

Method used

Low-temperature denitrification catalysts are used to construct strong metal/metal oxide/support mutually by constructing strong metal/metal oxide/support mutually The action is to regulate the catalytic active site, increase the surfactant site, improve the activity and anti-toxic properties of the catalyst, and add polypropylene fiber wire, ultra-fine activated carbon and aluminum sol to enhance the strength and wear resistance of the catalyst.

Benefits of technology

显著提高了低温脱硝效率和抗中毒性能,降低了脱硝温度,延长了催化剂的使用寿命,减少了能源消耗和碳排放,提高了催化剂的强度和耐磨性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385438800000021
    Figure BDA0004385438800000021
  • Figure BDA0004385438800000031
    Figure BDA0004385438800000031
  • Figure BDA0004385438800000032
    Figure BDA0004385438800000032
Patent Text Reader

Abstract

The present invention discloses a low-temperature denitration catalyst and a preparation method thereof. The catalyst comprises the following raw materials by weight: 60-70 parts of nano titanium dioxide, 0.5-2.5 parts of zirconium oxide, 0.5-3 parts of modified graphene, 0.02-0.1 parts of chloroiridic acid, 5-8 parts of ammonium heptamolybdate, 0.5-2.5 parts of ammonium metavanadate, 2-10 parts of cerium nitrate, 3-8 parts of polypropylene fiber, 1-4 parts of ultrafine activated carbon, 2-6 parts of aluminum sol, 1.5-5 parts of polyethylene oxide, and 1.2-3.5 parts of aminocellulose. The denitration catalyst prepared by the present invention has the characteristics of large specific surface area, high porosity, high low-temperature catalytic activity, strong anti-poisoning ability, high strength, etc., and is particularly suitable for use in the low temperature range of 100-180°C, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flue gas denitration catalysts, and particularly relates to a low-temperature denitration catalyst and a preparation method thereof. Background Art

[0002] NOx is the main pollutant that forms acid rain and photochemical smog, and can cause direct harm to the human body. Therefore, how to effectively control and manage NO has become an extremely important environmental and social issue in the world today. At present, the main methods used in flue gas denitrification technology are selective catalytic reduction (SCR), selective non-catalytic reduction (SNCR), SCR / SNCR mixed method technology, etc. SNCR is highly dependent on temperature and has a relatively low denitrification rate (only 40% to 60%). The selective catalytic reduction technology (SCR) has been widely used in many countries with strict flue gas emission standards and can meet higher emission standards. It is considered to be an economical and reliable denitrification technology. However, the V2O5 / TiO2 catalyst used by SCR can usually only be used in flue gas at 300℃ to 420℃. If denitrification is carried out in flue gas conditions below 300℃, serious sulfur oxide poisoning and water poisoning, as well as alkali (alkaline earth) metal poisoning will occur, and this poisoning is irreversible. However, the flue gas temperature at the denitration reactor of many industrial kilns is lower than 300℃, or even lower than 150℃. For example, the flue gas temperature of coke ovens, sintering machines, pelletizing machines, garbage incinerators, biomass boilers, hazardous waste incinerators, chemical furnaces, catalytic cracking furnaces, glass kilns, ceramic kilns, cement kilns, forging furnaces, casting furnaces, heat treatment furnaces, etc. is mostly between 120 and 300℃. In order to meet the ultra-low emission requirements of nitrogen oxides, the commonly used method is to heat the flue gas to 300℃ or above so that medium and high temperature catalysts can be used for denitration. In this way, a large amount of energy for heating will be consumed, and a large amount of carbon emissions will also be generated. It is a typical high-energy consumption and high-carbon emission type of emission reduction, which is inconsistent with my country's environmental protection policies of energy conservation and emission reduction and the development direction of sustainable green development.

[0003] Sintering machine, pelletizing machine and coke oven are among the most important equipment in the steel industry. They have large flue gas volume. The flue gas temperature of sintering and pelletizing is mainly in the range of 120-160℃. The concentration of nitrogen oxide emission is relatively high. According to the national environmental protection emission requirements, ultra-low emission control is required (the current emission standard is NOx≤50mg / Nm 3 ). Due to the low original flue gas temperature, if the traditional medium and high temperature SCR denitrification technology is used, the flue gas needs to be heated to at least 280℃. Flue gas heating will cause huge energy waste. If the flue gas of a 5 million ton pellet kiln is heated to 280℃ for medium and high temperature SCR denitrification using blast furnace and coke oven mixed gas, the annual gas consumption is about 53.03 million m 3 , based on the mixed gas price of 0.48 yuan / Nm3 It is calculated that the annual gas cost is 25.46 million yuan, the annual increase in carbon emissions is about 44,859 tons, and the cost of purchasing carbon emission indicators is about 2.24 million yuan per year.

[0004] In the past two years, my country has also begun to pay attention to the flue gas treatment of the cement industry and has put forward ultra-low emission requirements. The difficulty of environmental protection of cement kiln flue gas is still in denitrification, which is specifically manifested in the following aspects: (1) The flue gas temperature at the C1 outlet is about 300-400℃, which meets the flue gas temperature conditions for medium and high temperature SCR denitrification, but the dust concentration here is very high (about 120g / Nm 3 ), the catalyst is prone to clogging and wear, and the alkali metal and alkaline earth metal content in the dust is very high, which can cause fatal damage to the catalyst. Therefore, there are few successful application cases at home and abroad. The operating cycle of the catalyst is very short (about 6 to 10 months), resulting in frequent shutdowns of the production line and huge economic losses; (2) After the high-temperature fan and before the bag dust removal, the smoke temperature is about 200 to 250 ° C, and medium-temperature SCR denitrification can be carried out, but the dust concentration here is still very high (about 60g / Nm 3 ), the clogging and wear of the catalyst are still prominent, the poisoning of alkali metals and alkaline earth metals is obvious, the service life of the catalyst is still not long, and the operating cost is very high. For the problem of cement kiln flue gas treatment, the only real solution is to carry out low-temperature or ultra-low-temperature denitrification after the bag filter at the kiln tail. The dust concentration here is very low (<10mg / Nm 3 ), which has little effect on the catalyst, but the smoke temperature is also very low, generally between 100 and 160°C. Therefore, it is very necessary to invent a low-temperature denitrification catalyst with excellent performance as a technical guarantee.

[0005] In the prior art, low-temperature SCR denitration catalysts have poor denitration effect, low strength, small specific surface area and unsatisfactory anti-poisoning performance at low temperatures of 100-180°C. In order to meet the denitration needs of low-temperature, water-containing, sulfur-containing, and dust-containing complex flue gases in industries such as steel, cement, biomass, and waste incineration, it is hoped to develop a new denitration catalyst with a large specific surface area, high activity, good denitration effect under low or ultra-low temperature conditions, and excellent anti-poisoning performance. Summary of the invention

[0006] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a low-temperature denitration catalyst and a preparation method thereof. The obtained denitration catalyst has the characteristics of large specific surface area, high porosity, high low-temperature catalytic activity, strong anti-poisoning ability and high strength, and is particularly suitable for use in the low temperature range of 100 to 180°C.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0009]

[0010]

[0011] As a further preferred embodiment of the technical solution of the present invention, the following raw materials are included in parts by weight:

[0012]

[0013] As a further preferred embodiment of the technical solution of the present invention, the diameter of the polypropylene fiber is 5 to 10 μm and the length is 2 to 4 mm.

[0014] As a further preferred embodiment of the technical solution of the present invention, the particle size of the ultrafine activated carbon is 1000-2500 mesh.

[0015] As a further preferred embodiment of the technical solution of the present invention, the viscosity average molecular weights of polyethylene oxide and aminocellulose are 4,000,000-6,000,000 and 20,000-40,000, respectively.

[0016] As a further preferred embodiment of the technical solution of the present invention, the nano titanium dioxide is anatase structure; wherein the nano crystal grain size is 3 to 8 nm, and the specific surface area is 180 to 250 m 2 / g, SO3 content 2~4wt%.

[0017] As a further preferred embodiment of the technical solution of the present invention, the iridium content in the chloroiridic acid is ≥35wt%.

[0018] As a further preferred embodiment of the technical solution of the present invention, the zirconium content in the zirconium oxide is ≥ 80wt%, the particle size is 8-10nm, and the specific surface area is 50-80m 2 / g.

[0019] As a further preferred embodiment of the technical solution of the present invention, the preparation of modified graphene includes the following steps: adding 1500mL of 1.8g / L graphene oxide aqueous dispersion to 80g of urea, and reacting at 170°C for 4h; after the reaction, washing and filtering to obtain modified graphene.

[0020] At the same time, the present invention also provides a method for preparing the above-mentioned low-temperature denitration catalyst, comprising the following steps:

[0021] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 30 to 40 parts of deionized water and stirring them evenly to obtain a first mixture;

[0022] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 9 to 12 parts of 15 to 20 wt % ammonia water and stirring evenly, and then adding 10 to 20 parts of 90 to 95° C. deionized water until completely dissolved to obtain a second mixture;

[0023] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry;

[0024] S4. After aging the mud obtained in step S3 for 16 to 36 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 200 to 240 hours, and then calcined at 450 to 550° C. for 30 to 40 hours to obtain a low-temperature denitration catalyst.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention provides a low-temperature denitration catalyst, which is prepared by using iridium oxide, vanadium oxide, molybdenum oxide and cerium oxide as denitration active components, and titanium dioxide, modified graphene and zirconium oxide as carriers of the active components; specifically: since IrO2 has a face-centered cubic lattice structure, it is unable to fully expose more catalytic active sites, resulting in its catalytic activity failing to meet actual requirements; therefore, the present invention regulates the electronic properties of the catalytic active sites by constructing a strong metal / metal oxide / carrier interaction to redistribute electrons on the interface; the IrO2 nanoclusters undergo obvious lattice distortion through mutual doping of IrO2 nanoclusters, V2O5 and MO3 and strong interactions with the carrier, which is bound to be conducive to exposing more unsaturated coordination active sites; at the same time, the strong electron transfer (electron transfer from Ir to V) at the interface between IrO2 and V2O5 makes the IrO2 active site act as an electrophilic center, weakening the adsorption of oxygen-containing intermediates and changing the Ir The occupied number of eg orbitals expands the surface defects of the catalyst, increases the active sites on the catalyst surface, and further enhances the adsorption and transfer effect of the catalyst surface on NOx, NH3 and O2. Therefore, the catalyst of the present invention builds a new type of oxygen absorption and oxygen release platform, achieves better adsorption and transfer effects, effectively promotes the reaction rate of denitrification, significantly improves the denitrification effect and anti-poisoning performance, and greatly reduces the denitrification temperature of the catalyst.

[0027] ZrO2 has good mechanical strength due to its high strength and toughness. As a catalyst structural additive, it is compounded with nano-titanium dioxide and modified graphene to obtain a composite carrier for denitration catalyst with mesopores; wherein the modified graphene is obtained by modifying graphene oxide with urea, and the obtained modified graphene increases the alkali adsorption site, improves the denitration performance, and further improves the anti-poisoning ability of the catalyst. The composite carrier prepared by the present invention has efficient mass transfer, high activity, and high strength, and greatly improves the strength and wear resistance of the catalyst.

[0028] (2) The present invention provides a low-temperature denitration catalyst, which is added with polypropylene reinforced fiber with a wire diameter of 5 to 8 μm, ultrafine activated carbon with a particle size of 1000 to 2500 mesh, and aluminum sol, and is pre-mixed evenly. Its functions are: 1) The polypropylene reinforced fiber replaces the glass fiber that was commonly used before, which effectively solves the cracking phenomenon in the product manufacturing process. When the product dries and shrinks, the polypropylene reinforced fiber plays the role of a secondary reinforcing rib, which increases the gripping force between the fiber and the denitration catalyst matrix and prevents the generation of cracks; 2) The aluminum sol acts as a binder for nano-titanium dioxide and zirconium oxide powders, which significantly improves the overall strength and wear resistance of the denitration catalyst; 3) After the ultrafine activated carbon is infiltrated with aluminum sol, its dispersibility is improved and its oxidation resistance is improved. After drying and roasting, part of it is burned to become voids, which increases the porosity and pore volume of the catalyst, and part of it still retains the original activated carbon molecular structure, allowing the catalyst to adsorb or capture The ability to capture ammonia and NOx is enhanced, providing good synergy and auxiliary effects for the catalytic reaction of active sites, with unexpected technical effects; 4) The Al2O3 particles of the aluminum sol can mutually infiltrate the TiO2 particles to form a diffuse double electric layer, which increases the effective diameter of the particles. When the particles approach each other, they repel each other with like charges, which can effectively prevent the agglomeration of nanoparticles (usually 3-8nm TiO2 particles are very easy to agglomerate), which is beneficial to the stability of the dispersed system. This effect is better than the traditional method of adding nano-SiO2 or adding SiO2 when producing TiO2.

[0029] (3) The present invention provides a low-temperature denitration catalyst, which selects polyethylene oxide (PEO) and amino cellulose (ACMC) of a certain molecular weight, which are pre-mixed and stirred evenly before being added. This can prevent the agglomeration or hard core phenomenon that often occurs in the mud during the mixing process, significantly improve the plasticity and extrusion effect of the mud, significantly improve the yield rate, and effectively enhance the strength and wear resistance of the catalyst. Amino cellulose (ACMC) is used to solve the effect of alkali metals in carboxymethyl cellulose used in high-temperature catalysts on the activity of the catalyst, thereby improving the performance and service life of the catalyst.

[0030] In summary, the denitration catalyst provided by the present invention has a porous structure and a specific surface area of ​​80 to 90 m 2 / g. And it contains a large number of acidic active sites, thus showing excellent denitrification catalytic reaction efficiency and anti-poisoning ability at low temperatures, and is suitable for application in the range of 100-300℃. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0032] The test methods described in the following embodiments and application examples are conventional methods unless otherwise specified; the reagents described are commercially available unless otherwise specified.

[0033] The diameter of the polypropylene fiber is 5-10 μm and the length is 2-4 mm; the iridium content in the chloroiridic acid is ≥35 wt%; the nano-titanium dioxide is anatase-type structure, the nano-crystal size is 3-8 nm, and the specific surface area is 180-250 m 2 / g, SO3 content 2-4wt%; zirconium content in zirconium oxide ≥80wt%, particle size 8-10nm, specific surface area 50-80m 2 / g.

[0034] Meanwhile, unless otherwise specified, all parts in the present invention are parts by weight.

[0035] Example 1

[0036] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0037]

[0038]

[0039] Among them, the particle size of the ultrafine activated carbon is 1500 mesh; the viscosity average molecular weights of polyethylene oxide and amino cellulose are 4,000,000 and 20,000 respectively.

[0040] The preparation of modified graphene includes the following steps: adding 1500 mL of 1.8 g / L graphene oxide aqueous dispersion to 80 g of urea and reacting at 170° C. for 4 hours; after the reaction is completed, washing and filtering are performed to obtain modified graphene.

[0041] In this embodiment, a method for preparing the above-mentioned low-temperature denitration catalyst is also provided, comprising the following steps:

[0042] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 350 g of deionized water and stirring them evenly to obtain a first mixture;

[0043] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 100 g of 18 wt % ammonia water and stirring evenly, and then adding 150 g of 90° C. deionized water until completely dissolved to obtain a second mixture;

[0044] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry;

[0045] S4. After aging the mud obtained in step S3 for 24 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 200 hours, and then calcined at 550° C. for 30 hours to obtain a low-temperature denitration catalyst.

[0046] Example 2

[0047] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0048]

[0049]

[0050] Among them, the particle size of the ultrafine activated carbon is 1500 mesh; the viscosity average molecular weights of polyethylene oxide and amino cellulose are 4,000,000 and 20,000 respectively.

[0051] The preparation of modified graphene includes the following steps: adding 1500 mL of 1.8 g / L graphene oxide aqueous dispersion to 80 g of urea, and reacting at 170° C. for 4 hours; after the reaction is completed, washing and filtering are performed to obtain modified graphene.

[0052] In this embodiment, a method for preparing the above-mentioned low-temperature denitration catalyst is also provided, comprising the following steps:

[0053] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 300 g of deionized water and stirring them evenly to obtain a first mixture;

[0054] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 90 g of 18 wt % ammonia water and stirring evenly, and then adding 200 g of 90° C. deionized water until completely dissolved to obtain a second mixture;

[0055] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry;

[0056] S4. After aging the mud obtained in step S3 for 24 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 240 hours, and then calcined at 450° C. for 40 hours to obtain a low-temperature denitration catalyst.

[0057] Example 3

[0058] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0059]

[0060]

[0061] Among them, the particle size of the ultrafine activated carbon is 1500 mesh; the viscosity average molecular weights of polyethylene oxide and amino cellulose are 4,000,000 and 20,000 respectively.

[0062] The preparation of modified graphene includes the following steps: adding 1500 mL of 1.8 g / L graphene oxide aqueous dispersion to 80 g of urea, and reacting at 170° C. for 4 hours; after the reaction is completed, washing and filtering are performed to obtain modified graphene.

[0063] In this embodiment, a method for preparing the above-mentioned low-temperature denitration catalyst is also provided, comprising the following steps:

[0064] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 300 g of deionized water and stirring them evenly to obtain a first mixture;

[0065] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 90 g of 20 wt% ammonia water and stirring evenly, and then adding 200 g of 90° C. deionized water until completely dissolved to obtain a second mixture;

[0066] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry;

[0067] S4. After aging the mud obtained in step S3 for 24 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 220 hours, and then calcined at 500° C. for 35 hours to obtain a low-temperature denitration catalyst.

[0068] Comparative Example 1

[0069] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0070]

[0071]

[0072] Among them, the particle size of the ultrafine activated carbon is 1500 mesh; the viscosity average molecular weights of polyethylene oxide and amino cellulose are 4,000,000 and 20,000 respectively.

[0073] In this comparative example, a method for preparing the above-mentioned low-temperature denitration catalyst is also provided, comprising the following steps:

[0074] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide and 350 g of deionized water and stirring evenly to obtain a first mixture;

[0075] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 100 g of 18 wt % ammonia water and stirring evenly, and then adding 150 g of 90° C. deionized water until completely dissolved to obtain a second mixture;

[0076] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry;

[0077] S4. After aging the mud obtained in step S3 for 24 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 200 hours, and then calcined at 550° C. for 30 hours to obtain a low-temperature denitration catalyst.

[0078] That is, compared with Example 1, Comparative Example 1 omits the modified graphene, and other material types, amounts and preparation processes are the same.

[0079] Comparative Example 2

[0080] A low-temperature denitration catalyst, comprising the following raw materials, in parts by weight:

[0081]

[0082]

[0083] The viscosity average molecular weights of polyethylene oxide and aminocellulose are 4,000,000 and 20,000 respectively.

[0084] The preparation of modified graphene includes the following steps: adding 1500 mL of 1.8 g / L graphene oxide aqueous dispersion to 80 g of urea, and reacting at 170° C. for 4 hours; after the reaction is completed, washing and filtering are performed to obtain modified graphene.

[0085] In this comparative example, a method for preparing the above-mentioned low-temperature denitration catalyst is also provided, comprising the following steps:

[0086] S1, mixing nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 350 g of deionized water and stirring them evenly to obtain a first mixture;

[0087] S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 100 g of 18 wt % ammonia water and stirring evenly, and then adding 150 g of 90° C. deionized water until completely dissolved to obtain a second mixture;

[0088] S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading uniformly to obtain a mud material;

[0089] S4. After aging the mud obtained in step S3 for 24 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 200 hours, and then calcined at 550° C. for 30 hours to obtain a low-temperature denitration catalyst.

[0090] That is, compared with Example 1, the ultrafine activated carbon is omitted in Comparative Example 1, and other material types, dosages and preparation processes are the same.

[0091] The denitration catalysts according to Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 were subjected to performance testing and denitration experiments, and the results are shown in Table 1. The testing method is as follows:

[0092] (1) Denitrification efficiency determination: The simulated flue gas composition is: NOx, NH3, O2 and carrier gas N2, the air velocity is 7200h -1 , NOx concentration is 1250mg / m 3 , NH3 / NOx molar ratio = 1, O2 concentration: 6%, reaction temperature controlled at 100-280°C. The flow of each gas is controlled by a mass flow meter. Before the gas enters the reactor, it is mixed by a gas mixer and then preheated by a preheater. The NOx concentration at the inlet and outlet is measured by a flue gas analyzer. In order to eliminate the influence of surface adsorption, the system starts collecting and testing after the ventilation operation is stable for 30 minutes.

[0093] (2) Determination of sulfur and water resistance: The simulated flue gas composition is NOx, NH3, SO2, H2O, O2 and carrier gas N2, with an air velocity of 7200h -1 , NOx concentration is 1250mg / m 3 , NH3 / NOx molar ratio = 1, O2 concentration: 6%, SO2 concentration: 17000mg / m 3, H2O content: 20vol%; reaction temperature is controlled at 150℃. The flow rate of each gas is controlled by a mass flow meter. Before entering the reactor, the gas is mixed by a gas mixer and then preheated by a preheater. The NOx concentration at the inlet and outlet is measured by a flue gas analyzer. In order to eliminate the influence of surface adsorption, the system starts collecting and testing after the ventilation operation is stable for 30 minutes.

[0094] (3) Measure the strength and wear resistance of the catalyst: Cut three test pieces of each catalyst with a size of 150mm*150mm*150mm; use a pressure testing machine to test the axial and radial compressive strength. The wear test method refers to the wear rate determination in the national standard GB / T38219-2019: Cut two test pieces with a length and width of 65mm and a height of 100mm as test samples and comparison samples; Place the sample in a constant temperature oven at 105°C and dry for 2h, take it out and weigh it after naturally cooling to room temperature; Wrap the sample with kaolin cotton and place it in the sample bin. The wind speed in the catalyst channel is 15m / s and the wear agent concentration is 50g / m 3 , stop after 2 hours. Take out the sample, place it in an oven at 105℃ and dry it for 2 hours, take it out and cool it naturally to room temperature, and weigh it accurately to 0.01g. Use the same method to measure the wear rate of the blank sample block without adding the reinforcing agent.

[0095] Table 1

[0096]

[0097]

[0098] It can be seen from Table 1 that the low-temperature denitration catalyst prepared in the embodiment of the present invention has excellent denitration efficiency, sulfur and water resistance, and physical properties.

[0099] Although the present invention has been disclosed as above in the form of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A low-temperature denitration catalyst, characterized in that: The preparation includes the following raw materials in parts by weight: Raw material weight Nano titanium dioxide 60~70 Zirconia 0.5~2.5 Modified graphene 0.5~3 Chloroiridic acid 0.02~0.1 Ammonium heptamolybdate 5~8 Ammonium metavanadate 0.5~2.5 Cerium nitrate 2~10 Polypropylene fiber 3~8 Ultrafine activated carbon 1~4 Aluminum sol 2~6 Polyethylene oxide 1.5~5 Aminocellulose 1.2~3.5; Among them, the viscosity average molecular weights of polyethylene oxide and aminocellulose are 4,000,000-6,000,000 and 20,000-40,000 respectively; The preparation of modified graphene includes the following steps: adding 1500 mL of 1.8 g / L graphene oxide aqueous dispersion to 80 g of urea, reacting at 170° C. for 4 hours; after the reaction is completed, washing and filtering to obtain modified graphene; The low temperature of the low temperature denitration catalyst refers to 100-150°C.

2. A low-temperature denitration catalyst according to claim 1, characterized in that: The preparation includes the following raw materials in parts by weight: Raw material weight Nano Titanium Dioxide 65 Zirconia 1 Modified graphene 2.5 Chloroiridic acid 0.05 Ammonium heptamolybdate 7 Ammonium metavanadate 1 Cerium nitrate 8 Polypropylene fiber 5 Ultrafine activated carbon 2 Aluminum sol 3 Polyethylene oxide 3 Aminocellulose 2.

5.

3. A low-temperature denitration catalyst according to claim 1 or 2, characterized in that: The diameter of the polypropylene fiber is 5~10μm and the length is 2~4mm.

4. A low-temperature denitration catalyst according to claim 1 or 2, characterized in that: The particle size of ultrafine activated carbon is 1000 mesh to 2500 mesh.

5. A low-temperature denitration catalyst according to claim 1 or 2, characterized in that: Nano-titanium dioxide has an anatase structure, wherein the nano-crystal size is 3~8nm and the specific surface area is 180~250m2 / g.

6. A low-temperature denitration catalyst according to claim 1 or 2, characterized in that: The iridium content in chloroiridic acid is ≥35wt%.

7. A low-temperature denitration catalyst according to claim 1 or 2, characterized in that: The zirconium content in zirconium oxide is ≥80wt%, the particle size is 8~10nm, and the specific surface area is 50~80 m2 / g.

8. A method for preparing the low-temperature denitration catalyst according to any one of claims 1 to 7, characterized in that: The steps include: S1. Mix nano titanium dioxide, cerium nitrate, zirconium oxide, modified graphene and 30 to 40 parts of deionized water and stir them evenly to obtain a first mixture; S2, mixing chloroiridic acid, ammonium heptamolybdate, ammonium metavanadate and 9-12 parts of 15-20wt% ammonia water and stirring evenly, and then adding 10-20 parts of 90-95°C deionized water until completely dissolved to obtain a second mixture; S3, adding the second mixture obtained in step S2 to the first mixture obtained in step S1, and then adding polypropylene fiber, ultrafine activated carbon, aluminum sol, polyethylene oxide, and amino cellulose, and then stirring and kneading them evenly to obtain a slurry; S4. After aging the mud obtained in step S3 for 16 to 36 hours, the mud is extruded into a honeycomb shape, and the temperature is raised to 65° C. and dried for 200 to 240 hours, and then calcined at 450 to 550° C. for 30 to 40 hours to obtain a low-temperature denitration catalyst.

Citation Information

Patent Citations

  • Preparation process of nano catalyst honeycomb

    CN101703927A

  • Low-temperature denitration catalyst and preparation method thereof

    CN107570142A

  • High-low temperature denitration catalyst and preparation method thereof

    CN110773211A

  • Denitration catalyst

    JP2022159206A